BATASAN KARAKTERISTIK DAN FAKTOR YANG BERHUBUNGAN (ETIOLOGI) DIAGNOSA KEPERAWATAN: HAMBATAN MOBILITAS FISIK PADA PASIEN STROKE - Agianto; Sari, Selvia Harum; Wahid, Abdurahman (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2015)
Accurate clinical indicators are needed to validate the establishment of nursing diagnosis. Theaccuracy of clinical indicators is determined by the presence of defining characteristics and relatedfactors (etiology). A valid nursing diagnosis is essential to reduce the risk ofmisdiagnosis. The studyaimed to investigate the main defining characteristics and etiology of nursing diagnosis impairedphysical mobility that appeared in stroke patients. This was a descriptive study (documentation study)with retrospective approach. There were 26 documentation notes ofstroke patient used in this study.The results showed that the main defining characteristics that appear in stroke patients were difficultyturning (100%), limited ability to perform fine motor skills (100%), limited ability to perform grossmotor skills (100%), decrease in range of motion (26,9%), and slowed movement (3,8%). The mainetiologies that appeared in stroke patients were decreased muscle strength (92.3%), neuromuscularimpairment (80,8%), pain (19,2%), joint stiffness (3,8%), and sensoriperceptual impairment (3,8%).Nurses are expected to focus on the main defining characteristics and etiology that appear whenperforming the assessment in stroke patients with impaired physical mobility nursing diagnosis inorder to plan effective nursing actions.